Promotional language and Maqasid Shariah in the advertisements of local and international halal food products - Wan Mohd Fadzlullah, Wan Nor Fasihah; Ariffin, Adlina (2019)
Abstract​: The halal industry is a booming global trade that is known to be profitable to various market sectors. With the aspiration to be the Global Halal Hub by 2020, Malaysia will undoubtedly benefit from the strategic marketing of halal food products. One of the aspects that are known to influence consumers into purchasing halal food products is the choice of linguistic terms used in these advertisements. This research looks into one hundred promotional materials of local and international halal food products collected from several halal food exhibitions around Klang Valley. The keywords used to describe the food products in the advertisements were analyzed using a corpus analysis software (AntConc) to find out how the halal concept is translated and presented in the food products advertisement. The findings of this research shows the marketing strategy in local and international brands specifically in the use of ‘halal’ as a persuasion device in the advertisement of their products. Apart from educating consumers on the halal concept, the rightful marketing of halal food products will also help Muslims to observe the obligatory ‘halalan toyyiban’ while inevitably benefiting the global consumers as a whole.